Selective localization of aluminum oxide at interface and its effect on thermal conductivity in polypropylene/polyolefin elastomer blends. (1st April 2019) - Zhang, Xi; Maira, Bulbul; Hashimoto, Yuya; Wada, Toru; Chammingkwan, Patchanee; Thakur, Ashutosh; Taniike, Toshiaki
Abstract: A reactor granule technology (RGT) was applied to immiscible polypropylene (PP)/polyolefin elastomer (POE) blends to effectively control the localization of nanoparticles at the interface. The RGT afforded uniform dispersion of in-situ generated aluminum oxide (Al2 O3 ) nanoparticles in PP, and this guaranteed the migration of nanoparticles to the interface of a co-continuous structure when blended with POE. The selective localization of nanoparticles at the interface was confirmed by transmission electron microscope (TEM), scanning electron microscope (SEM), elemental mapping (EDX) and thermal gravimetric analysis (TGA). Such localization was never achieved when preformed Al2 O3 nanoparticles were used, and this fact stresses the importance of uniform dispersion in controlling the migration of nanoparticles. The migration was also affected by the viscosity of POE: POE having higher viscosity resulted in a smaller domain size, and thereby more nanoparticles could migrate to the interface without agglomeration. The impacts of the selective localization at the interface and the phase domain size on the thermal conductivity of the resultant nanocomposites were studied and discussed.